Knitted fragments of clothes excavated from the Swedish 17th century flagship Kronan - Lundin, Helena (Archaeological Textiles Review, 2018)
Clothing excavated from the Swedish flagship Kronan, which sank in 1676 as the result of an explosion, includes fragments of civilian garments such as knitted headgear, gloves, stockings and embroidered silk waistcoats belonging to some of the 800 crewmen who died. The location and distribution of these fragments suggest which types of knitted clothing belonged to men of different social standing in the late 17th century.